2005
DOI: 10.1149/1.2077307
|View full text |Cite
|
Sign up to set email alerts
|

Active Form of Ru for the CH[sub 3]OH Electro-oxidation Reaction

Abstract: In this work, unsupported Pt∕Ru catalysts are used to address the issue of Ru oxide involvement during the methanol oxidation reaction, from the point of view of both Ru “oxidation state” (metal vs oxide) and amount of Ru oxide. It is shown that a simple electrochemical method is useful as in situ probe for the Ru oxidation state. The method also yields insight into the Pt to Ru site distribution of the catalyst surface. The results indicate that the electrochemical formation of reversibly reducible Ru oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Dinh et al concluded that the catalytic activity for methanol oxidation was adversely affected because of blockage of active metal sites by such oxide materials. 141 Using a simple in situ electrochemical method, Bock et al found that formation of ruthenium oxides during methanol oxidation is insignificant and very little or no supportable ruthenium oxide appeared at methanol concentrations larger than 0.1 M. 210 Furthermore, they found that RuO 2 formed at a potential larger than 0.6 V inhibited methanol oxidation and that metallic Ru is the active state in the Pt−Ru catalyst to form −OH species for complete oxidation of methanol to CO 2 . Kim et al previously summarized these results and studied Ru-decorated Pt (111) substrates for methanol oxidation by XPS.…”
Section: Effect Of Ruomentioning
confidence: 99%
“…Dinh et al concluded that the catalytic activity for methanol oxidation was adversely affected because of blockage of active metal sites by such oxide materials. 141 Using a simple in situ electrochemical method, Bock et al found that formation of ruthenium oxides during methanol oxidation is insignificant and very little or no supportable ruthenium oxide appeared at methanol concentrations larger than 0.1 M. 210 Furthermore, they found that RuO 2 formed at a potential larger than 0.6 V inhibited methanol oxidation and that metallic Ru is the active state in the Pt−Ru catalyst to form −OH species for complete oxidation of methanol to CO 2 . Kim et al previously summarized these results and studied Ru-decorated Pt (111) substrates for methanol oxidation by XPS.…”
Section: Effect Of Ruomentioning
confidence: 99%
“…The XPS spectra show the order of metallic Ru for the three samples is Aerosol Pt-Ru > commercial Pt-Ru black > commercial 80% Pt-Ru/C. Although there are few studies on the most active form of Ru for methanol oxidation by Pt-Ru alloys, studies on model single-crystal Pt-Ru surfaces have indicated that the presence of Ru in metallic state is required for methanol electro-oxidation [109,110]. Some experiments have shown a decrease in methanol oxidation activity due to prior formation (i.e.…”
Section: Structural and Compositional Analysis Of Templated Pt-rumentioning
confidence: 98%
“…Some experiments have shown a decrease in methanol oxidation activity due to prior formation (i.e. before continuous operation) of Ru oxides is very small (<5%) and is only observable at potentials above 0.6V vs. RHE [110]. Alternative studies have shown that additional oxidation treatments in air resulted in enhanced electrochemical activity for Pt-Ru/C catalysts which was attributed to further segregation of Ru to surface and formation of RuO 2 [108].…”
Section: Structural and Compositional Analysis Of Templated Pt-rumentioning
confidence: 99%
“…Takai et al have briefly reported on the synthesis of mesoporous Ru black with surface area of 62 m 2 g -1 via lyotropic crystal templating as the end member of the Pt-Ru alloy [23]. In addition to metallic Ru, high surface area ruthenium oxide is also an important material for various applications, including electrocatalysts for chlorine evolution [24], electrochemical capacitor electrodes [25][26][27][28][29], as well as fuel cell electrocatalysts [30][31][32][33][34][35][36][37][38][39]. The small particle size (1-2 nm) and the existence of appreciable pores are important requirements for the high capacitance [40][41][42].…”
Section: Introductionmentioning
confidence: 99%